Language learning strategies and language proficiency of polytechnic students in Johor / Hamizah Zahari - Zahari, Hamizah (2012)
This study investigated the language learning strategies and English Language proficiency of students learning English as a Second Language (ESL) at a polytechnic located in the state of Johor in Malaysia. The study also explored the most frequent language learning strategies employed by the ESL students in three different academic settings i.e. inside the formal classroom, outside the classroom and for English language examinations. This study involved 86 ESL learners from varying Diploma programs under the technical and vocational stream in a polytechnic located in Johor. The study employed a mixed-method research paradigm which involved two surveys; SILL (Strategy Inventory of Language Learning) by Oxford (1989) and Language Learning Strategy Questionnaire and semi structured interviews with six respondents. Data was analyzed using inferential statistics employing the statistical software package SPSS for Windows (version 16). The results indicated that these students employed similar language learning strategies despite the differences in language proficiency- i.e. Affective strategies, Social strategies and Metacognitive strategies. However, the Advanced students were reported to have used more strategies in comparison to Elementary level proficiency students who were unaware of the best strategies to be used at given situations. There were no significant differences in the language learning strategies employed by the three groups based on their proficiency levels. The most frequently used language learning strategies employed by ESL students inside the formal classroom were Compensatory and Metacognitive strategies whilst Affective and Compensatory strategies were the most frequently used strategies outside the classroom. The result also revealed that the ESL students used Compensatory and Memory strategies when preparing for English examination. In the classroom environment, Metacognitive strategies and the Compensatory strategies in this study are significantly different among the three groups of language proficiencies. The findings of this study suggest that ESL students especially Elementary proficiency level ESL students be provided with more strategy training programmes. The findings also indicated that more emphasis should be given to memory strategy training so that it can be used effectively in their everyday activities.